Analyzing enablers of logistics parks in improving supply chain competitiveness in India: Enhancing Supply Chain Efficiency through Logistics Parks in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This research paper aims to analyze the enablers of logistics parks in improving supply chaincompetitiveness in India. With the rapid growth of the Indian economy and the increasing complexity ofsupply chain operations, logistics parks have emerged as critical hubs to enhance supply chainefficiency and overall competitiveness. The study investigates key factors that enable logistics parks toplay a pivotal role in streamlining logistics operations and fostering a more competitive environment forbusinesses.